Handover Practices for Psychiatric Admissions: A Retrospective Review of Communication Gaps - Aalap Asurlekar (BJPsych Open)
Aims: This study assesses the frequency and adequacy of handovers for newly admitted patients in a community psychiatry hospital, focusing on formal communication to the duty doctor.